Metabolic syndrome and psoriasis severity in South-East Asian patients: An investigation of potential association using current and chronological assessments - Leena Chularojanamontri (2018)
© 2016 Japanese Dermatological Association Although studies regarding prevalence of metabolic syndrome (MS) in Asian psoriatic patients are limited and show varying results, a previous report describes a significant increase in prevalence of MS in Thai psoriatic patients, as compared with rates in the general population. However, no significant association between MS and psoriasis severity using the Psoriasis Area and Severity Index (PASI) was found, which differs from the findings of Korean and Japanese studies. This study aimed at re-evaluating the association between MS and psoriasis severity in Thai patients using current assessment (PASI) and chronological assessment (historical course and interventions). A total of 273 psoriatic patients were recruited. After controlling for age and sex, 96 patients were assigned to the MS group and 96 patients to the non-MS group. Similar to the previous study, no significant differences were identified between metabolic and non-metabolic patients regarding PASI, age of onset, disease duration and family history of psoriasis. However, the numbers of hospitalizations (P = 0.018) and interventions (P = 0.028) were significantly higher in metabolic patients than in non-metabolic patients. Further, a greater number of metabolic components was significantly associated with a higher number of hospitalizations (P = 0.012), pustular or erythrodermic psoriasis episodes (P = 0.049), and interventions (P = 0.005). Body mass index of 23 kg/m2or more, abdominal obesity and high blood pressure were associated with an increased risk of treatment failure. Using chronological assessment, our study supported that MS negatively affects psoriasis severity and treatment outcomes. Screening for MS is highly recommended for psoriatic patients.